ANALYSIS OF FACTORS INFLUENCING AGRICULTURAL EXTENSION PERFORMANCE IN THE USE OF CYBER EXTENSION IN MALANG RAYA REGION - S Sabir; S Sugiyanto; K Sukesi; Y Yulianti (Socio-Economics/Agribusiness Department, 2019)
The potency for developing cyber extension should be utilized by agricultural extension worker in order to enrich extension material. However. It seems that the development of cyber extension was experiencing various obstacles. Based on that condition, this study aims to analyze the factors influencing the performance of cyber extension in utilizing cyber extension. The types of data used in this study were primary and secondary data. Primary data was obtained by conducting interviews with respondents. 87 respondents were determined purposively. Secondary data was obtained from documents on extension activites in Malang Raya Region. Path analysis was used in this study to answer the research objectives. Most respondents are still classified young, have a relative high education level and have a work period of less than 12 years. The result showed cyber extension socialization, personal interaction and perception of agricultural extension worker factors significantly influenced agricultural extension worker behavior. Meanwhile, factors of cyber extension socialization, perception the of agricultural extension worker and the behavior of agricultural extension worker significantly influenced the performance of agricultural extension worker in utilizing cyber extension. Only socialization and the perception of agricultural extension worker had both direct and indirect influences, where the socialization factor was the only factor with the greatest total influence value on the performance of agricultural extension worker in utilizing cyber extension. The performance of agricultural extension worker in utilizing cyber extension needed to be improved, one of which was through socialization. Socialization effort was carried out in order to increase understanding of cyber extension usefulness to agricultural extension worker. In addition, to stimulate the use of cyber extension, it was necessary to provide incentives to agricultural extension workers who utilize cyber extension.